Promoting Sustainable Agriculture through Community-Based Liquid Organic Fertilizer Production from Household Organic Waste in Metut Village, North Kalimantan - Alfi Rumidatul; atmawi darwis; Anca Awal Sembada; Anne hadiyane; Mustika dewi; Imra Imra; Mustika Dewi (PT Inovasi Pratama Internasional, 2026)
The accumulation of unmanaged household organic waste remains a persistent environmental challenge in rural areas, including Metut Village, Mentarang Hulu District, North Kalimantan, Indonesia, where organic waste is commonly burned or indiscriminately discarded. At the same time, local farmers continue to depend on relatively expensive chemical fertilizers. This community service program aimed to improve residents’ knowledge and practical skills in converting household organic waste into liquid organic fertilizer (LOF) as an affordable and environmentally friendly alternative for sustainable agriculture. The program employed a combination of community education and hands-on training implemented through four stages: socialization and educational counseling, training and demonstration, supervised independent practice, and evaluation using pre-test and post-test assessments. A total of 28 participants, consisting of housewives, farmer group members, and village youth, were involved in the program. The results demonstrated a substantial increase in participants’ knowledge, with average scores improving from 46.4 in the pre-test to 86.1 in the post-test. Participants successfully produced liquid organic fertilizer independently using kitchen waste fermented with a bioactivator for 14–21 days and subsequently applied the product to home garden crops. The program contributed to reducing household organic waste generation, lowering fertilizer expenditures, and promoting environmentally sustainable agricultural practices. These findings indicate that liquid organic fertilizer training is an effective approach for community empowerment and sustainable waste management in rural communities.